Non-violent discipline options for caregivers and teachers: a systematic overview of the evidence and exploration of the role of attunement - Quail, Karen (Department of Psychology, 2021)
Violence against children is a widespread problem with devastating consequences, and corporal punishment is a risk factor for more serious forms of physical abuse. One reason for the persistence of corporal punishment may be lack of awareness of positive disciplinary alternatives. At the other extreme, lack of awareness of positive options may lead to permissive parenting, which also has negative outcomes for children. The primary objective of this research was to find, and explore the state of the science on, individual non-violent interventions for challenging behavior, in so doing forming a “toolkit” for use by caregivers and teachers. To meet this objective, a systematic overview of systematic reviews was conducted. In the course of the overview, aside from information on the individual discipline tools, data relevant to attunement was collected and explored. Attunement describes sensitive responsiveness of caregivers towards their children, understanding and matching the child's needs and signals with appropriate responses. Results of the overview show that a wide range of evidence-supported interventions exist, many of which have been found effective with severely challenging behavior. Further, evidence was found suggesting the importance of attunement in optimal use of these discipline tools. Practical implications of these findings are discussed and gaps in the research highlighted.